ATIVIDADE FITOESTROGÊNICA DE Morus nigra L., MORACEAE, EM RATAS OVARIECTOMIZADAS - SILVA, Selma do Nascimento (2012)
The hypoestrogenism in climacteric is associated with vasomotor symptoms, cardiovascular disease, osteoporosis and urogenital changes. At this stage of life of women, hormone replacement HRT can alleviate some consequences of decreased estrogen caused by ovarian failure. However, estrogen therapy may cause adverse effects such as breast tenderness, uterine bleeding and increase the relative risk for cancers of the breast and endometrium. Morus nigra L. (mulberry) is a plant species most used in Brazil for the treatment of menopausal symptoms. Thus, this study aims to assess the likely effects phytoestrogenics the hydroalcoholic extract (HE) from the leaves of M. nigra in ovariectomized female rats. Therefore, the dried leaves were pulverized and soaked in 70% ethanol in the proportion 1:3 (v/v) to obtain the HE (yield=21.90%). The HE was subjected to evaluation of the antioxidant activity by capturing free radical 2,2-diphenyl-1-picryl-hidrazil, analyzed by liquid chromatography coupled to mass spectrum (LC-MS/MS) for identification of compound and then partitioned with hexane, chloroform, ethyl acetate and methanol/water. The safety of extract was determined by the test of acute toxicity in mice at doses of 0.1 to 10.0 g/kg orally (p.o.). To evaluate the estrogenic activity of the extract from M. nigra leaves, the rats were divided into two control groups: sham-operated (SHAM) and ovariectomized (OVX), which received 0.1 mL/100 g saline, and two test groups: ovariectomized and treated with a solution estroprogestative (OVX-EP-50g/kg) and ovariectomized and treated with HE M. nigra 500mg/kg (OVX-HE500), n = 8-10, daily, p.o., for 14 weeks. Throughout the treatment period were analyzed the frequency stage of the estrous cycle, food intake and body weight. At the end of treatment were evaluated biochemical parameters and hormone, histomorphometry of the uterus, vagina and breast. Furthermore, the influence of M. nigra on the proliferation of breast tumor cell line MCF-7 was determined by MTT method. HE showed high antioxidant activity when compared to standard quercetin. The analysis by LC-MS/MS EH compared with literature data allowed the identification of flavonoids (kaempferol and quercetin) and quinic acid derivatives (caffeoylquinic acid and isomers dicaffeoylquinic acid). In the analysis of the estrous cycle, the group OVX-HE500 showed an increase in proestrous and estrous phases at 15.25% and 26.6%, respectively, when compared to OVX group. Ovariectomy caused an increase in body mass, which was prevented by treatment with HE and EP solution. The weight of abdominal adipose tissue was also significantly lower in groups OVX-HE and OVX-EP compared to the OVX group. Ovariectomy also induced atrophy of uterine tissue (OVX group) compared to SHAM group, indicating the efficiency of the surgical procedure, and the administration of EP significantly increased uterine weight compared with OVX group. Average uterine weight of the OVX-HE group was also higher than the OVX group, but smaller than the OVX-EP group. In the histological analysis, it was observed that the characteristics of the squamous epithelium of the vagina of OVX-EP group (57.79 ± 1.49m), relative to thickness, were similar to that of SHAM group (50 66 ± 1.60m). After 14 weeks of administration of HE was a partial reversal of vaginal atrophy (37.34 ± 1.77m), when compared to the OVX group (12.92 ± 0.53m), showing maturation of this tissue with the treatment, however, the HE did not alter breast tissue, unlike the stimulus EP-induced. Regarding biochemistry was observed that the treatments (HE and EP) reduced concentrations of triglycerides in 27.5% and 23.8% respectively, when compared to OVX. In in vitro tests, the data indicate that the HE M. nigra acts as a weak phytoestrogen and protects against cell proliferation of human breast carcinoma (MCF-7). In acute toxicity study, the treatment of mice with HE did not produce behavioral changes or deaths. Together, the data demonstrate that the HE M. nigra L. has beneficial effects in models of induced menopause in rats, decreased uterine and vaginal atrophy, without changing the mammary structure, improving triglyceride levels and shows up secure and potent oxidant activity. These effects may be related to their flavonoid constituents, and thus the plant species may be useful in controlling symptoms of menopause as an alternative to Hormone Replacement Therapy.